SİNGERS FORMANT: A COMPULSION OR PREFERENCE? - Şahin SARUHAN (Fırat University, 2019)
In literature the function of singer’s formant has been described on its contribution to singer to be hearable on accompanied orchestra. In another suggestion that also has a strong relation to mentioned explanation, this function was explained by claimed physio-acoustical relation between outer ear canal and laryngeal cavity. But, it is seen that, there are many of question that were not answered by now, in relation to socio-cultural and historical background of singer’s formant. In this context, whether SF was the only one or the best option that can be functioned in the case of loud orchestral accompaniment is one of the most important matters. To answer the questions that whether it was the a preference decided by another reasons related to musical parameters of opera art shaped by its historical background or not, and whether this preference was made in spite of another option or options, is an important task in musicological domain. In this study singer’s formant was scrutinized in these relations. It was concluded that, to explain only with its acoustical and physiological aspects will be not enough to complete understanding of singer’s formant.